Collaborative Governance in Renewable Energy Utilization - Achmad; Aries Djaenuri; Tjahya Supriyatna; Muchlis Hamdi (International Journal of Science and Society, 2020)
This study aims to analyze collaborative governance between the Regional Government and the State Electricity Company and the Biogas Power Plant in utilizing renewable energy in Rantau Sakti Village, North Tambusai District, Rokan Hulu Regency, Riau Province, Indonesia. This research was conducted using qualitative methods. Data collection techniques used in this study were interviews, observation and documentation study. Collaboration between the Regional Government and the State Electricity Company and the Biogas Power Plant in utilizing new and renewable energy has not yet been formed in a whole and comprehensive manner. If the Biogas Power Plant already has legality and clarity on the legal status and its management as a result of a change in the Regional Government Law which causes the authority in the energy sector to be drawn to the provincial level, the Regional Government of Rokan Hulu Regency loses management rights over the Power Plant Biogas.